Aspects of delictual liability in pharmacy practice - Lewis, Melissa Geane (Rhodes University, Faculty of Law, Law, 2007)
The thesis explores the various instances in which pharmacists may incur delictual liability for harm suffered by their patients or third parties. As such, it is primarily concerned with the field of professional negligence. The work focuses specifically on the wrongfulness, fault and causation enquiries in pharmacy malpractice cases. The discussion is set against the backdrop of the pharmacy profession's shift towards patient-orientated service in recent years and explores whether this change in the profession's social role has had any effect on the legal duties and standard of care to which pharmacists are currently bound. It is argued that, in light of the dangers posed by modern medicines and the extent to which pharmacists are professionally expected to involve themselves in patient care, pharmacists can no longer escape liability simply by accurately dispensing pharmaceutical products. Rather, they are expected to participate actively in avoiding drug-related injury by, for example, providing patient counselling, detecting invalid or erroneous prescriptions and monitoring prescription refills. Although the thesis places particular emphasis on the role of pharmacists in achieving risk management, it also argues that pharmacists are, in very limited circumstances, required to participate in the risk assessment process traditionally thought to fall exclusively into the realm of physicians. It is furthermore demonstrated that pharmacists can incur liability regardless of whether a patient's harm can also be partially attributed to the blameworthy conduct of another healthcare professional. Although the thesis concludes that pharmacists are currently exposed to greater risks of liability than they were in the past, it also shows that plaintiffs who seek damages from pharmacists will usually experience a number of difficulties in establishing liability. In particular, problems are likely to be encountered in satisfying a court as to the presence of factual causation, which is notoriously difficult to establish in drug-related cases.
Keywords: Pharmacy -- Practice; Pharmacist and patient; Pharmacy -- Social aspects; Pharmacists -- Malpractice; Pharmacy -- Law and legislation